Dramatizing Historical Distance - Frank, Marcie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
This essay explores the efficacies of the distance rubric Mark Salber Phillips developed in On Historical Distance by applying it to a couple of recent examples that post-date the book’s appearance: Ruth Scurr’s John Aubrey: My Own Life and Mike Leigh’s Mr. Turner. These examples lead to some speculations about Phillips’ attention to media and his account of the history of literary history.